Multiple Instagram Accounts and the Illusion of Freedom - Muria Endah Sokowati; Sefia Manda (Universitas Muhammadiyah Yogyakarta, 2022)
This article is motivated by the phenomenon of the ownership of multiple accounts on Instagram among teenagers. Previous research mentioned that a second Instagram account is used to express oneself without worrying that the identity of the users will be recognized by the public. Users feel they can upload anything on Instagram’s second accounts without following Instagram rules’ pressure of perfection. The second accounts become a sphere for users to perform their self-authenticity. The researchers inquire how teenagers use and manage their multiple Instagram accounts as a sphere for exploring themselves. Reflecting on the practice of surveillance between users through social media, including Instagram, the researchers argue that second Instagram accounts function as the sphere for pseudo-liberations for its users. Hence, the researchers also question how freedom is experienced in that sphere. The researchers use digital ethnography to get the answers to the questions. As a result, since the self is socially constructed and self-authentic, the researchers found that second accounts are not liberating their users. The constructed self-authenticity has shifted from the control of their parents and other adults; to their peers’ surveillance.